Development of Canva-based Audiovisual Media to train the Ability to Understand Narrative Text Information - Kristi, Tabita; Purwati, Panca Dewi (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This research is based on students' difficulty in understanding narrative text. The purpose of this research is to describe the design, feasibility test results, and effectiveness test results of developing audiovisual media for the history of the Old City of Semarang based on Canva on the ability to understand narrative text information for grade V students of SDN Jomblang 02 Semarang. This research method is Research and Development (R&D) guided by Sugiyono's research with a modified Borg and Gall design up to step 8. The research subjects are fifth grade students of SDN Jomblang 02 Semarang. Data collection techniques in this study include observation, interviews, documentation, questionnaires, and tests. The validation results from media experts and material experts were 95% and 83% respectively with a very feasible category. The effectiveness test on small-scale and large-scale trials at SDN Jomblang 02 Semarang with an increase in the average pretest and postest, respectively 45 and 90. The results of the Wilcoxon t-test calculation were <0.05, namely 0.000 so that Ha was accepted and Ho was rejected. The n-gain increase is 0.8136 which is above 0.7 in the high category. So it can be concluded that the audiovisual media of the history of the Old City of Semarang based on canva on the ability to understand the information of narrative text of fifth grade students of SDN Jomblang 02 Semarang is effective. The implications of this research consist of theoretical, practical, and pedagogical implications.